(untitled) (Texas Journal of Philology, Culture and History, 2022)
The article is devoted to the consideration of the fundamental factors that contributed to the further spread of Arab-Muslim culture, which to some extent helped the Arabs to popularize the conditionally "new" dogma and thereby realize the Arab-Muslim culture as a civilizational aspect of world history in the period of early Islam. he scientific work shows the legitimization of the Arab-Muslim culture on the example of the initial Arab-Muslim pact between the Prophet Muhammad and the administrative aristocracy of Mecca, which turned out to be the starting point for the further emission of the young culture of the Arabian Peninsula. The legitimization of Arab-Muslim relations and the spread of Arabic literary language throughout the territory of the Caliphate had a favorable effect on the development of medieval Arab-Muslim science, helped the communication of scholars and the establishment of ties between the centers of science of the empire. Linguistic unity facilitated the development of the Greek-Iranian cultural heritage by the inhabitants of the empire, which, thanks to the works of Arab translators, became the property of educated Muslims, regardless of their ethnicity or religious beliefs. Immediately after the first legal assertion as an instrument of cultural creativity, Arabic literary language contributed to the convergence of groups of the population that were distant in ethnic and linguistic terms, which ultimately led to the creation of an Arab-Muslim cultural region